Theorizing Cultures of Political Violence in Times of Austerity Studying Social Movements in Comparative Perspective - Rak, Joanna (Taylor & Francis, 2018)
After the multidimensional financial crisis of 2008, the member states of the Eurozone imposed a set of economic policies to save their economies. Socially unpopular cuts contributed to the occurrence of violent movements that both opposed austerity policies and created animosity towards the politicians who implemented them. Combining qualitative and quantitative comparative analyses from anti-austerity movements in 14 Eurozone states from 2007 to 2015, Joanna Rak develops an original typology of patterns of a culture of political violence to explain why some anti-austerity movements turned to violence and others did not, despite having shared goals and political values. She uncovers the very nature of the differences and similarities between cultures of political violence, identifies their sources, and determines their differing results. Simultaneously, she opens a discussion on the exploratory and explanatory utility of the category of a culture of political violence in the Social Sciences. Theorizing Cultures of Political Violence in Times of Austerity casts new light on the scholarly debate on cultures of political violence and anti-austerity violent behavior, making it a compelling read for scholars of political sociology, political behavior, comparative politics, European politics, and sociology.